SOCIAL ADAPTATION AND ITS CORRELATION TO THE SOCIAL AND ECONOMIC LEVEL OF THE VISUALLY IMPAIRED - Maryam Neamah Joudah Alawadi, (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims at identifying the connection between the aspects of organizing the social environment for visually impaired students and the formation of their positive socialization. The sample of the study consisted of students with visual impairments (35) (age 7-9 years) specialized schools in the Republic of Iraq: a school with the basics of elementary adaptation for special education (18 students) and a Nazim Al-Tabakli primary school (17 students). The students had visual impairments: myopia, astigmatism, inflammation of the cornea of ??the eye, photophobia and difficulty focusing eye movements. The results of the study indicate that, orienting his pedagogical activity towards the formation of the need for achievements in visually impaired students, the teacher must be sure that a high level of motivation is necessary for him for further successful educational activity. It is important to understand that with a high level of developmental need for success and less developed ability, the visually impaired student will be more capable of achieving success, well-being, and an effective learning process.